Method for preparing porous copper foil by electroetching in a water sol system

Through the electrostatic etching method in the water -soluble system, the use of water -soluble gel additives such as Huangyuan and Guaer gum to dissolve in the electrolyte, forming a chain -shaped long chain structure with a negative charge, solving the cumbersome and cumbersome methods of porous copper foil preparation methods and craftsmanship. The problems that are difficult to control in the pores and the uniform pores and high consistency of porous copper foil are realized.

CN115182032BActive Publication Date: 2025-01-24QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210838463.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-01-24
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

The existing porous copper foil preparation methods are cumbersome, economically cost-effective, and difficult to control the morphology and pore size.

Method used

In the water -soluble system, porous copper foil is prepared by electrostatic engraving methods, and water -soluble gel additives such as Huangyuan gum and Gwaer gum are dissolved in the electrolyte to form a chain -shaped long chain structure with a negative charge. Essence

Benefits of technology

The efficient preparation of porous copper foil has been achieved, the pore diameter is evenly distributed, the distribution of the aperture is narrow, the consistency is high, and the process is convenient, fast and controllable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115182032B_ABST
    Figure CN115182032B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing porous copper foil by electro-etching in a hydrosol system. The method comprises: at least a copper material as an anode, a cathode, and an electrolyte are used to jointly construct an electrochemical reaction system, wherein the electrolyte comprises sulfuric acid, a hydrosol additive, and water, and the hydrosol additive comprises any one or a combination of two of xanthan gum and guar gum; the electrochemical reaction system is energized to perform an electro-etching reaction, thereby shaping a porous morphology on the surface of the anode copper foil to obtain a porous copper foil. The method of the present invention adds hydrosol additives such as xanthan gum and guar gum to the electrolyte, and utilizes the characteristics of xanthan gum, guar gum, etc., which present a network long-chain structure and carry a negative charge after being dissolved in an aqueous solution, to finally obtain a porous copper foil. The preparation process of the present invention is convenient, fast, and controllable. Due to the template effect of the hydrosol network, the pore size distribution range of the obtained porous copper foil is narrow and the consistency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing copper foil, in particular to a method for preparing porous copper foil by electro-etching in a water sol system, belonging to the technical field of copper foil preparation. Background Art

[0002] Porous copper foil can be used as a single metal to catalyze CC coupling due to its high specific surface area, multiple active sites, and the reaction characteristics of copper itself, and has broad application prospects in the future field of carbon neutrality. In addition, porous copper foil can also be used in the field of metal lithium batteries. The porous copper foil negative electrode current collector with moderate pore size can effectively inhibit the generation of lithium dendrites, greatly improving the possibility of high energy density metal lithium batteries to be applied.

[0003] Existing methods for preparing porous copper foil, such as printing template method, powder sintering method, dealloying method, etc., are either cumbersome or too costly. Traditional methods also use different chemical or electrochemical methods to prepare porous copper foil, which are divided into etching and deposition. These methods are relatively simple and have low economic costs, but there are problems with the morphology and pore size of porous copper foil that are difficult to control. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing porous copper foil by electroetching in a water sol system, thereby overcoming the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] The embodiment of the present invention provides a method for preparing a porous copper foil by electro-etching in a water sol system, which comprises:

[0007] At least a copper material as an anode, a cathode, and an electrolyte together constitute an electrochemical reaction system, wherein the electrolyte comprises sulfuric acid, a hydrosol additive, and water, and the hydrosol additive comprises any one of xanthan gum and guar gum or a combination of two thereof;

[0008] The electrochemical reaction system is energized to perform an electro-etching reaction, thereby forming a porous morphology on the surface of the anode copper foil to obtain a porous copper foil.

[0009] In some preferred embodiments, the electrolyte further includes a selectively added or unadded dissolution promoter, and the dissolution promoter includes any one of glycerol and glucose or a combination of the two.

[0010] In some preferred embodiments, the electrolyte further includes a structure enhancer which is selectively added or not added, and the structure enhancer includes sodium caseinate.

[0011] The embodiment of the present invention also provides a porous copper foil prepared by the above method.

[0012] Compared with the prior art, the beneficial effects of the present invention are at least:

[0013] The present invention provides a method for preparing a porous copper foil by electro-etching in a hydrosol system. The method comprises adding hydrosol additives such as xanthan gum and guar gum to an electrolyte, utilizing the characteristics that the xanthan gum and guar gum present a long-chain network structure and carry a negative charge after being dissolved in an aqueous solution, and finally preparing the porous copper foil. The preparation process of the present invention is convenient, fast and controllable. Due to the template effect of the hydrosol network, the prepared porous copper foil has uniform pore size, a narrow pore size distribution range and high consistency. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 This is a diagram showing the effect of a negatively charged network structure migrating toward the anode in a method for preparing a porous copper foil by electro-etching in a water sol system according to a typical embodiment of the present invention;

[0016] Figure 2a-2b This is a SEM image of the porous copper foil prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0017] In view of the deficiencies in the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice, which mainly provides a method for preparing porous copper foil by electro-etching in a hydrosol system. The inventors of this case have found that xanthan gum, guar gum, etc., which present a network long-chain structure and carry a negative charge after being dissolved in an aqueous solution, can be used to apply them to the method of preparing porous copper foil by anode electro-etching. The long-chain molecules of the hydrosol with a network structure carrying a negative charge will adsorb to the surface of the anode, protecting the adsorbed area, while the remaining unprotected exposed areas will be etched, and finally a porous structure will be etched on the surface of the anode copper foil. The effect of the migration of the negatively charged network structure to the anode is as follows: Figure 1 shown.

[0018] The technical solution, its implementation process and principle will be further explained as follows.

[0019] One aspect of an embodiment of the present invention provides a method for preparing a porous copper foil by electro-etching in a hydrosol system, comprising: at least a copper material as an anode, a cathode, and an electrolyte jointly construct an electrochemical reaction system, wherein the electrolyte comprises sulfuric acid, a hydrosol additive, and water, and the hydrosol additive comprises any one of xanthan gum and guar gum or a combination of two thereof;

[0020] The electrochemical reaction system is energized to perform an electric etching reaction, thereby etching a porous morphology on the surface of the anode copper foil to obtain a porous copper foil.

[0021] In some preferred embodiments, the electrolyte further includes a selectively added or unadded dissolution promoter, including but not limited to any one of glycerol and glucose or a combination of both, for promoting the dissolution of the hydrosol additive. In some preferred embodiments, the electrolyte further includes a selectively added or unadded structure enhancer, including but not limited to sodium caseinate, which can be used to enhance the stability of the hydrosol network, making it less susceptible to the influence of the surrounding environmental factors, and realizing product preparation in a wider range of conditions.

[0022] In some preferred embodiments, the method specifically comprises:

[0023] providing an aqueous solution of sulfuric acid;

[0024] adding a hydrosol additive, a dissolution promoter, and a structure enhancer into water for dissolution to form an additive solution;

[0025] The additive solution is added into the sulfuric acid aqueous solution and mixed thoroughly to obtain the electrolyte.

[0026] In some preferred embodiments, the concentration of sulfuric acid in the aqueous sulfuric acid solution is 20-150 g / L.

[0027] In some preferred embodiments, the concentration of the hydrosol additive in the electrolyte is 0.5-500 mg / L, the concentration of sodium caseinate is 0.1 mg / L-200 mg / L, and the concentration of the dissolution promoter is 0.1-2000 mg / L.

[0028] In some preferred embodiments, when performing the electro-etching reaction, the cell voltage used is 0.2-2.0V.

[0029] In some preferred embodiments, during the electro-etching reaction, the temperature of the electrolyte is 10-60°C.

[0030] In some preferred embodiments, the electro-etching reaction time is 2 to 60 minutes.

[0031] Furthermore, the copper material includes copper foil, but is not limited thereto.

[0032] Furthermore, the material of the cathode includes other inert metals such as stainless steel, titanium or platinum, but is not limited thereto.

[0033] Furthermore, the shape of the anode includes a sheet shape or an arc shape, but is not limited thereto.

[0034] Among them, in some more specific implementation cases, the method for preparing a porous copper foil by electroetching in a water sol system specifically comprises the following steps:

[0035] Step 1: Use copper foil as the anode; use stainless steel or other inert metals such as titanium, platinum, etc. as the cathode. The anode shape can be sheet or arc;

[0036] Step 2, using a sulfuric acid aqueous solution as an electrolyte, wherein the sulfuric acid concentration is between 20 and 150 g / L;

[0037] Step 3, using one or two of xanthan gum and guar gum as the main hydrosol additives, using glycerol or glucose to promote dissolution, and sodium caseinate as a structural enhancer, and adding water to dissolve. Add the prepared additive solution to the sulfuric acid aqueous solution, mix thoroughly to ensure that the hydrosol concentration is between 0.5 and 500 mg / L, the sodium caseinate concentration is between 0.1 mg / L and 200 mg / L, and the glycerol or glucose concentration is between 0.1 and 2000 mg / L;

[0038] Step 4: After the system is fully mixed, a porous morphology is formed on the surface of the copper foil by electro-etching, the cell voltage is between 0.2 and 2.0 V, the electrolysis temperature is between 10 and 60° C., the electro-etching reaction time is 2 to 60 minutes, and the obtained product is a porous copper foil.

[0039] Furthermore, the porous copper foil prepared by the present invention has a porous structure, and the pores contained in the porous structure have a pore size of 4-8 microns. The pore size distribution of the porous copper foil prepared by the present invention is more uniform and consistent in size, that is, the pore size distribution range is narrow and the consistency is high. At the same time, the part except the pores is a dense copper layer, and the mechanical properties of the material are good.

[0040] In summary, through the above technical scheme, the method of preparing porous copper foil by electroetching in a hydrosol system of the present invention adds hydrosol additives such as xanthan gum and guar gum to the electrolyte, and utilizes the characteristics of xanthan gum, guar gum, etc. that present a network long-chain structure and carry a negative charge after being dissolved in an aqueous solution, and finally prepares a porous copper foil. The porous copper foil obtained by this preparation method has a more uniform pore size distribution and consistent size, that is, the pore size distribution range is narrow and the consistency is high.

[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and several preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. For the test methods in the following embodiments that do not specify specific conditions, the test methods in the embodiments are all carried out under normal conditions. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0042] All reagents used in the following examples were of analytical grade.

[0043] Example 1

[0044] Use metal copper foil as anode; stainless steel as cathode, and the anode shape is sheet; use sulfuric acid aqueous solution as electrolyte, and the concentration of sulfuric acid is 20g / L; mix xanthan gum, guar gum, sodium caseinate and glycerol in proportion, and add water to dissolve. Add this solution to the sulfuric acid aqueous solution, the total concentration of xanthan gum and guar gum is 500mg / L, the concentration of sodium caseinate is 0.1mg / L, and the concentration of glycerol is 2000mg / L; after the system is fully mixed, the surface of the copper foil is treated by electro-etching, the cell voltage is 0.2V, the electrolyte temperature is 10°C, the electro-etching time is 60min, and the obtained product is a porous copper foil with good morphology. The microstructure (SEM image) of the porous copper foil obtained in this example is as shown Figure 2a and Figure 2b As shown, the pore size distribution range is narrow and the consistency is high, with a pore size of 4-8 microns.

[0045] Example 2

[0046] The metal copper foil is used as the anode; titanium is used as the cathode, and the anode shape is arc-shaped; sulfuric acid aqueous solution is used as the electrolyte, and the concentration of sulfuric acid is 150g / L; xanthan gum, sodium caseinate and glycerol are mixed in proportion and dissolved in water. The solution is added to the sulfuric acid aqueous solution, the concentration of xanthan gum is 0.5mg / L, the concentration of sodium caseinate is 100mg / L, and the concentration of glycerol is 0.1mg / L; after the system is fully mixed, the copper foil surface is treated by electro-etching, the tank voltage is 0.8V, the electrolyte temperature is 60℃, and the electro-etching time is 2min. The obtained product is a porous copper foil with good morphology.

[0047] Example 3

[0048] The metal copper foil is used as the anode; platinum is used as the cathode, and the anode shape is sheet-shaped; sulfuric acid aqueous solution is used as the electrolyte, and the concentration of sulfuric acid is 70g / L; guar gum and glucose are mixed in proportion and dissolved in water. The solution is added to the sulfuric acid aqueous solution, the concentration of guar gum is 200mg / L, and the concentration of glucose is 100mg / L; after the system is fully mixed, the copper foil surface is treated by electro-etching, the tank voltage is 2.0V, the electrolyte temperature is 25℃, and the electro-etching time is 30min. The obtained product is a porous copper foil with good morphology.

[0049] Comparative Example 1

[0050] This comparative example is basically the same as Example 1, except that no xanthan gum or guar gum is added.

[0051] The etched pore sizes of the obtained copper foil are different, the particle size distribution range is wide, and the morphology consistency is poor.

[0052] Comparative Example 2

[0053] This comparative example is basically the same as Example 1, except that the total concentration of xanthan gum and guar gum is 0.3 mg / L. The hydrosol content is too low and the pore size distribution range is too wide.

[0054] Comparative Example 3

[0055] This comparative example is basically the same as Example 1, except that the total concentration of xanthan gum and guar gum is 550 mg / L. The hydrosol concentration is too high, the electrolyte is viscous, and convective mass transfer is difficult, which is not conducive to the experiment.

[0056] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0057] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the present invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention. Therefore, it is not intended herein to limit the present invention to the specific disclosed embodiments for carrying out the present invention, but rather it is intended that the present invention will include all embodiments within the scope of the appended claims.

Claims

1. A method for preparing porous copper foil by electroetching in a water sol system, characterized in that include: At least a copper material as an anode, a cathode, and an electrolyte are used to jointly construct an electrochemical reaction system, wherein the electrolyte comprises an aqueous sulfuric acid solution, a hydrosol additive, and water, the hydrosol additive comprises any one or a combination of two of xanthan gum and guar gum, the concentration of sulfuric acid in the aqueous sulfuric acid solution is 20 to 150 g / L, and the concentration of the hydrosol additive in the electrolyte is 0.5 to 500 mg / L; The electrochemical reaction system is energized to perform an electro-etching reaction, thereby shaping a porous morphology on the surface of the anode copper foil to obtain a porous copper foil. When performing the electro-etching reaction, the cell voltage used is 0.2 to 2.0 V, the temperature of the electrolyte is 10 to 60° C., and the electro-etching reaction time is 2 to 60 minutes.

2. The method for preparing porous copper foil by electroetching in a water sol system according to claim 1, characterized in that: The electrolyte also includes a selectively added or unadded dissolution promoter, and the dissolution promoter includes any one of glycerol and glucose or a combination of the two.

3. The method for preparing porous copper foil by electroetching in a water sol system according to claim 2, characterized in that: The electrolyte also includes a structure enhancer that is selectively added or not added, and the structure enhancer includes sodium caseinate.

4. The method for preparing porous copper foil by electroetching in a water sol system according to claim 3, characterized in that: include: providing an aqueous solution of sulfuric acid; adding a hydrosol additive, a dissolution promoter, and a structure enhancer into water for dissolution to form an additive solution; The additive solution is added into the sulfuric acid aqueous solution and mixed thoroughly to obtain the electrolyte.

5. The method for preparing porous copper foil by electro-etching in a water sol system according to claim 3, characterized in that: The concentration of the hydrosol additive in the electrolyte is 0.5-500 mg / L, the concentration of sodium caseinate is 0.1 mg / L-200 mg / L, and the concentration of the dissolution promoter is 0.1-2000 mg / L.

6. The method for preparing porous copper foil by electroetching in a water sol system according to claim 1, characterized in that: The copper material includes copper foil.

7. The method for preparing porous copper foil by electroetching in a water sol system according to claim 1, characterized in that: The cathode is made of stainless steel, titanium or platinum.

8. The method for preparing porous copper foil by electroetching in a water sol system according to claim 1, characterized in that: The shape of the anode includes a sheet shape or an arc shape.

9. The method according to any one of claims 1 to 8, characterized in that: The porous copper foil has a porous structure, and the pores contained in the porous structure have a pore size of 4 to 8 μm.

Citation Information

Patent Citations

  • Method for preparing multi-hole copper foil through square wave electro-chemistry etching

    CN110983422A

  • Electrolytic process and apparatus for forming pattern on surface of metallic object

    US4997529A